ANALYSIS OF FOOTSTEPS IN BASKETBALL PLAYERS: FEASIBILITY STUDY - Nuraminazkiya, Muhammad Zulfa Rangga; Pristianto, Arif (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
Basketball is a popular sport that provides numerous health benefits, but it also carries a high risk of injuries, particularly to the lower extremities. This study aimed to analyze the plantar pressure distribution in basketball players to identify potential risk factors for lower extremity injuries. A descriptive analytical study with a feasibility study design was conducted on 5 amateur basketball players aged 14-18 years. Plantar pressure was measured using the Zebris static stance platform, and postural assessments were performed using a scoliometer and goniometer. The results showed that basketball players tend to have a higher plantar pressure on the heel region, indicating a tendency to shift their body weight backward during standing. Additionally, the study revealed some variability in spinal and knee posture angles, suggesting the potential for muscle imbalances. These findings highlight the importance of implementing comprehensive training programs focused on strengthening the lower limb muscles, improving proprioception and balance, and enhancing core stability to prevent injuries and optimize athletic performance. The study provides valuable insights for coaches and healthcare professionals working with basketball players.